2D Porous Carbons prepared from Layered Organic–Inorganic Hybrids and their Use as Oxygen‐Reduction Electrocatalysts. Issue 28 (29th May 2017) - Li, Shuang; Cheng, Chong; Liang, Hai‐Wei; Feng, Xinliang; Thomas, Arne
Abstract : 2D porous carbon nanomaterials have attracted tremendous attention in different disciplines especially for electrochemical catalysis. The significant advantage of such 2D materials is that nearly all their surfaces are exposed to the electrolyte and can take part in the electrochemical reaction. Here, a versatile active‐salt‐templating strategy to efficiently synthesize 2D porous carbon nanosheets from layered organic–inorganic hybrids is presented. The resulting heteroatom‐doped carbon nanosheets (NFe/CNs) exhibit exceptional performance for the oxygen‐reduction reaction and in Zn–air battery electrodes. The activity of the best catalyst within a series of NFe/CNs exceeds the performance of conventional carbon‐supported Pt catalysts in terms of onset potential (0.930 vs 0.915 V of Pt/C), half‐wave potential (0.859 vs 0.816 V of Pt/C), long‐time stability, and methanol tolerance. Also, when applied as a cathode catalyst in a zinc–air battery the NFe/CNs presented here outperform commercial Pt/C catalysts. Abstract : The formation of layered organic–inorganic hybrids and their subsequent pyrolysis is suggested as a universal and scalable strategy for the synthesis of 2D porous carbon nanosheets with well‐defined 2D morphology, nanometer thickness, high surface area, and tunable heteroatom doping. These 2D carbon nanomaterials show remarkable electrocatalytic performances in the oxygen‐reduction reaction and outperform commercial state‐of‐the‐art Pt/C catalyst in zinc–air batteries.